Persepsi Guru Terhadap Kepemimpinan Pengajaran Pengetua Dalam Mempengaruhi Prestasi Akademik Pelajar Di Sekolah Menengah Dalam Kawasan Bandaraya Ipoh - Letchumanan, Manoharan (1995)
The purpose of this study was to determine the teacher’s perceptions of their principal’s instructional leadership role on students’ performance in academic. The principal’s instructioanl leadership is one of the main task of a principal and it is key factor to school effectiveness. The study involved a total of 240 teachers, chosen from 10 secondary schools in Ipoh, Perak through stratified sampling. Each teacher responded to his or her principals instructional leadership survey that consists of 33 questions. All the data were analyzed with descriptive statistics, pearson correlation, bivariate and multiple regression. The findings indicate that principals were perceived to be performed instructional leadership role regularly in monitoring standard of teaching, promoting positive school climate and providing resource for the teaching and learning in schools. However, evaluating and providing feedback, observing teachers in the classroom, supervising classroom teaching are perceived to be performed to a lesser extent by the principal. The bivariate regression analysis shows that principal’s instructional leadership role significantly influences the students’ performance in academic. This finding shows that effective schools tend to depend largely on the strong and initiating leadership of principals.